1965
DOI: 10.1111/j.1440-1754.1965.tb02579.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Insuffiency in Prematurity

Abstract: EDITORIAL SYNOPSIS Pulmonary function and respiratory mechanics have been examined, in detailed fashion, in infants of low birthweight shortly after birth and at intervals during the first year. A spectrum of deranged physiology, from that detected only by pulmonary function tests to overt respiratory illness for some time after birth, is thought to be due to mechanical disadvantages in the thorax and airways of immature babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

1966
1966
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 29 publications
2
36
0
1
Order By: Relevance
“…It is unlikely that this explanation would apply to gas trapping for the prolonged periods noted in this study. A second explanation for prolonged gas trapping is provided by the work of Burnard et al [4]. They showed that the airways of immature infants are very compliant, much like the chest wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that this explanation would apply to gas trapping for the prolonged periods noted in this study. A second explanation for prolonged gas trapping is provided by the work of Burnard et al [4]. They showed that the airways of immature infants are very compliant, much like the chest wall.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed to describe the adaptation of the newborn lung to the extrauterine environment have repeatedly shown a fall in thoracic gas volume (TGV) in the days after birth [4,16]. This decrease in volume can frequently be noted clinically as a decrease in the size of the chest, especially in smaller premature infants.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation with body length3 was the closest. This function of length [7] 38.5 0.040&0.010 BURNARD et al [5] 27 5.2f 1.3 0.063 COOK et al [lo] 4.9 SWYER et al [29] 4.9 KARLBERG and KOCH [20] Presentstudy 3013.3 0.05610.010…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant relation between pulmonary conductance and TGV. A significant relation between airway conductance and FRC has been reported previously in older children and adults [5]. The term specific conductance is applied to this relation.…”
Section: Piielan Williamsmentioning
confidence: 99%
See 1 more Smart Citation